Mechanical properties investigation of the potential extruded MgAZ31B as a bone implant - Fauzi Ibrahim; Anang Ansyori; Adi Prastyo; Lukito Dwi Yuono (TURBO [Tulisan Riset Berbasis Online], 2022)
Mg is a light metal that has superior properties, including low density, good ductility, medium strength, and good corrosion resistance, mg can also be combined to obtain better properties. Interest in the application of MgAZ31B for bone replacement has now become a major topic and continues to be intensified to improve results that are more compatible with bone constituents found in humans. In the human body, there are approximately 206 bones in an adult. Calcium, magnesium, and phosphorus are the main elements in the formation of human bones but there are many other elements in their formation, the real bone matrix is made of protein, collagen, calcium phosphate, calcium carbonate, magnesium salts, and other minerals. When viewed from the element of bone magnesium is an important part of bone formation and certainly not harmful to the main elements of human bones. However, before being used as bone implants, magnesium must pass the mechanical and clinical test stages.